Sterile hypopyon iridocyclitis during the treatment of pseudophakic bullous keratopathy with hydrophylic bandage lens - (:unkn) unknown (My University, 2002)
Hydrophilic bandage lenses have proven to be a useful treatment modality in bullous keratopathy for pain relief and visual improvement. Some complications may arise after the application of bandage lenses. We present a sterile hypopyon iridocyclitis case in a pseudophakic bullous keratopathy using a bandage contact lens.
Keywords: Bandage contact lens; Hypopyon iridocyclitis